The difference of low density lipoprotein cholesterol levels on different severity of coronary artery disease patients in Siloam Hospital Lippo Village - Michael Tanaka; Wilbert Santoso; Novita Anggraini (Fakultas Kedokteran Universitas Pelita Harapan, 2022)
Background: Coronary artery disease (CAD) is one of the highest causes of death in the world. Hypercholesterolemia, especially low-density lipoprotein (LDL) levels, is a major risk factor, because it is the main precursor of atherosclerosis. Previous studies showed the relationship between LDL level and the number of vessel disease is still inconsistent, therefore it needs to be observed further. The objective of this study was to know the effect of LDL levels on the number of vessel disease in CAD patients who underwent coronary angiography.Methods: It was a cross-sectional and retrospective study, where data were taken from medical records of CAD patients who underwent coronary angiography at Siloam Hospital Lippo Village between January to June 2018. Patients with at least one vessel disease were included. The number of vessel disease was categorized into 3 groups: one-vessel, two-vessels, and multi-vessel. The relationship between LDL levels and the number of vessel disease was analyzed using one way ANOVA.Result: The data includes 90 patients; 70 (77.8%) were male with average age of 56±9 years. There were 32 (35.6%) patients in one-vessel group; 27 (30%) in two-vessel group; and 31 (34.4%) in multi-vessel group with an average LDL levels of 106.43±40.51 mg/dl; 111.15±39.43 mg/dl; and 114.52±32.55 mg/dl respectively. Although it seemed that the increase in LDL cholesterol levels was in line with the number of vessel disease, there was no statistically significant relationship between the two variables (p=0.694).Conclusions: LDL cholesterol level does not affect the number of vessel disease in CAD patients.